Upaya Penanganan dalam Meningkatkan Keterampilan Sosial pada Anak Disabilitas Intelektual Ringan: Literature Review - Dita Pratiwi; Putri Ayu Debie Mustika Sari; Qanita Aulya Ulhaq; Hanifa Laura Dalimunthe (Lembaga Yasin AlSys, 2026)
Children with mild intellectual disability (MID) often experience difficulties in social skills, which affect their ability to establish relationships, communicate, and adapt to the social environment. This study aimed to identify various effective treatment efforts to improve social skills in children with MID. This study used the Systematic Literature Review method by searching for articles through Google and Google Scholar using specific keywords. The articles were selected based on inclusion criteria, including publication years from 2015 to 2025, subjects ranging from children to adults, and a study focus on improving social skills in children with MID. From an initial 14,418 articles, 15 articles matched the title and were analyzed further. The review results showed that interventions such as peer tutoring, storytelling, modeling, educational games, digital technology, and collaboration between schools and families were effective in improving the social skills of children with mild intellectual disability. Contextual, enjoyable, and sustainable approaches help children understand social norms, improve communication skills, and build independence in social interaction. Thus, selecting appropriate, adaptive, and sustainable treatment efforts is important to optimally support the social-emotional development of children with MID.